Effect of green promotion, green products and brand awareness on the decision to purchase Le Minerals in the Pasuruan region - Edwin Dwi Kusharianto; Tofan Tri Nugroho; Dewi Komala Sari (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the influence of green promotion, green products, and brand awareness on purchasing decisions for Le Minerale products in the Pasuruan region. A quantitative approach was employed using purposive sampling, involving 96 respondents who had previously purchased Le Minerale products. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that green promotion, green products, and brand awareness each have a positive and significant effect on purchasing decisions. Collectively, these variables explain 67.2% of the variance in purchasing decisions, highlighting the importance of environmentally oriented marketing strategies and strong brand recognition in influencing consumer behavior. The findings suggest that consumers are more likely to purchase Le Minerale products when they perceive the products as environmentally friendly and are familiar with the brand. This study contributes to the understanding of green marketing by demonstrating the combined role of environmental promotion, sustainable product attributes, and brand awareness in shaping purchasing decisions. Future research is recommended to include broader geographical coverage and additional variables to provide a more comprehensive understanding of consumer purchasing behavior. Keywords: Green Promotion; Green Product; Brand Awareness; Purchasing Decision; Le Minerale; Pasuruan; Green Marketing